Catastrophic disasters as opportunities for sustainable reconstruction: The case of Typhoon Yolanda - Santiago, Andrea L. (Animo Repository, 2015)
The after effects of Typhoon Yolanda have forced the country to rethink its strategy with respect to serious calamities. We believe that the country should also think about the devastation as an opportunity for shifting to “sustainable reconstruction” by which infrastructure is rebuilt with the long-term view, taking into account the impact of reconstruction on the environment, economy, society, technology, and institutions at each stage of the process. This approach is far better than recreating the status quo ante. In response, the Philippine government crafted the Yolanda Comprehensive Rehabilitation and Recovery Plan, which incorporates current best practices. The strategic shift is to increase investments in disaster mitigation, prevention, and preparedness rather than mere response, rehabilitation, and recovery. The evaluation of the 8,000 page, 8-volume document reveals a model that looks beyond physical structures and works toward rebuilding a community that learns to live sustainably. The challenge is ensuring that the sustainable reconstruction plans are implemented as envisioned. © 2015 by De La Salle University.